Psychological wellbeing, assertiveness and academic performance in university students of San Marcos - Velásquez C., Carlos (2008)
In this investigation the relations between the psychological well-being are examined, the assertiveness and the academic yield in the students of representative Faculties of the diverse areas of study of the University of San Marcos. For it, the Scale of Psychological Wellbeing of Ryff (that measures positive relations, autonomy, dominion of the surroundings, personal growth and intention in the life), the Inventory of Asertividad de Rathus and the academic yield were used. The study is of corelational descriptive type, with a circumstantial nonprobabilística sampling of the studied population to. The data were process with statistical package SPSS (Statistical for Package the Social Sciencies), making a correlation analysis and getting to be that yes significant correlation exists, p < 0.05, between the study variables, accepting the raised general hypothesis. In addition one was that significant relation between the psychological well-being and the assertiveness exists, as much in men as in the women. Of equal way in all the faculties the relation is significant between the variables in study, except in the faculty of industrial engineering the relation between assertiveness and academic yield did not turn out to be significant